Polyphenolic Compound from Vitis vinifera L. have Potential for the Alzheimer Disease Treatment - Ondrej, Soukup; Radomira, Stralkova; Tereza, Mistova; Marek, Popov; Alena, Hejtmankova; Jaromir, Lachman; Blanka, Klimova; Kamil, Kuca (Letters in Drug Design & Discovery, 2017)
Background: Grape marc and the wine cakes are known for high content of catechins, which have been reported to have many beneficial effects for human health. The most important are the effects on cardiovascular system. Also some potential to combat the Alzheimer´s disease has been reported for catechins contained in a green or white tea. Objective: To extract polyphenols from the wine grape seeds and try to characterize basic targets, which play an important role in AD. Methods: Using HPLC method we have identified and assessed the content of various catechins in the wine cake and grape seeds extracts. Applying in vitro methodologies we have evaluated the potency of the extract to inhibit acetylcholinesterase and prolyl oligoesterase. We also assessed the effect on the cell viability (MTT test) and its antioxidant activity (DPPH test) Results and Conclusion: It was shown that Pinot Gris, Pinot Noir and Hibernal are the varieties containing most of the polyphenolic compounds. Catechin followed by epicatechin and epigallocatechin were the most abundant polyphenols in the cake extract. We also report the biological activity of the extract with regard to a potential to improve cognitive decline associated with neurodegenerative disease like the Alzheimer´s disease. Apart from the expected antioxidant activity, there is an interesting prolyl oligopeptidase affinity, which can be an added value for targeting the cognitive decline.
Keywords: polyphenols